Community Empowerment in the Writing of Pararem in the Belatungan Traditional Village - I Ketut Sukadana; Luh Putu Suryani; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
Traditional village is a traditional village in Bali which has been autonomous since its inception. Each traditional village has its own management and assets, and has the authority to make awig-awig. The situation of program partners does not yet have a pararem as a rule for implementing awig-awig. The purpose of this program is to empower indigenous village communities so that they have a regulation in the form of pararem. The methods used in this service program are by: (1) giving lectures or legal counseling about the importance of a pararem in life in a traditional village, (2) carrying out focus group discussions (FGD) on pararem design, and (3) providing assistance in making traditional village pararem. The results of the program activities are the arrangement of a pararem awig enumerator with a total of 45 pawos (article).